Genome characterization of Long Island tick rhabdovirus, a new virus identified in Amblyomma americanum ticks - Tokarz, Rafal (BioMed Central, 2014)
BACKGROUND: Ticks are implicated as hosts to a wide range of animal and human pathogens. The full range of microbes harbored by ticks has not yet been fully explored. METHODS: As part of a viral surveillance and discovery project in arthropods, we used unbiased high-throughput sequencing to examine viromes of ticks collected on Long Island, New York in 2013. RESULTS: We detected and sequenced the complete genome of a novel rhabdovirus originating from a pool of Amblyomma americanum ticks. This virus, which we provisionally name Long Island tick rhabdovirus, is distantly related to Moussa virus from Africa. CONCLUSIONS: The Long Island tick rhabdovirus may represent a novel species within family Rhabdoviridae.